Brain and Critical Thinking in Education: A Bibliometric Review and Wordcloud Analysis - Sesrita, Afridha; Supena, Asep; Sumatri, Mohamad Syarif; Gumelar, Gumgum; Wibowo, Firmanul Catur (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2024)
AbstractThis article uses data from the Scopus database for bibliometric review and wordcloud analysis visualization of publications related to Brain and Critical Thinking in Education (BCTE). The study highlights the importance of the brain in the learning process and critical thinking, as well as identifying research trends, key topics, and geographic distribution of authors over the decade 2013-2023. With a focus on English-language publications, the study reveals that